Pan-Cancer Analysis of the Oncogenic and Immunological Role of RCN3: A Potential Biomarker for Prognosis and Immunotherapy - Ding, Jian; Meng, Yan; Han, Zelong; Luo, Xiaobei; Guo, Xuxue; Li, Yiwen; Liu, Side; Zhuang, Kangmin (Frontiers in Oncology, 2022)
Despite emerging publications have elucidated a functional association between RCN3 and tumors, no evidence about a pan-cancer analysis of RCN3 is available. Our study first conducted a comprehensive assessment of its expression profiles, prognosis value, immune infiltration and relevant cellular pathways via bioinformatics techniques based on the public database of TCGA (The cancer genome atlas). RCN3 is highly expressed in most tumors, and it is associated with poor prognosis. Kaplan-Meier analysis and Cox regression analysis suggested that the high expression of RCN3 was associated with poor overall survival (OS) in pan-cancer, Cox regression analysis also indicated high RCN3 expression was correlated with disease-specific survival (DSS), and progression-free interval (PFI) in most tumors. We observed a regulation function of RCN3 at genetic and epigenetic levels through CNA and DNA methylation using cBioPortal database. Based on Gene Set Enrichment Analysis, we first identified related pathways of RCN3 and its potential biological functions in pan-cancer, RCN3 was implicated in oncogenic pathways, and was related to extracellular matrix and immune regulation. We found that RCN3 positively correlated with the levels of infiltrating cells such as TAMs and CAFs, but negatively correlated with CD8+ T-cells by analyzing immune cell infiltration data we downloaded from published work and online databases, further investigation of the correlation between immunosuppressive genes, chemokines, chemokines receptors and high RCN3 expression showed a significant positive association in the vast majority of TCGA cancer types, these results indicated its role as an immune regulatory in cancers and suggested that RCN3 is a potential biomarker for immunotherapy. Also, we found that expression of RCN3 was much higher in CRC tissues than that in normal tissues with a higher expression level of RCN3 closely correlating to advanced American Joint Committee on Cancer (AJCC) stage, poor differentiation, increased tumor size and poor prognosis of CRC. Biological function experiments showed that RCN3 regulated CRC cells’ proliferation and metastasis ability. Upregulation of RCN3 in CRC cells increased the expression of immune related factor, including TGFβ1, IL-10 and IL-6. Thus, our pan-cancer analysis offers a deep understanding of potential oncogenic roles of RCN3 in different cancers.